Analisis Model Pembelajaran Inkuiri Terbimbing Terhadap Keterampilan Proses Sains Siswa pada Mata Pelajaran IPA SMP: (Analysis of Guided Inquiry Learning Models on Students' Science Process Skills in Science Subjects in Junior High School) - Suwardani Suwardani; Asrial Asrial; Upik Yelianti (BIODIK, 2021)
From the search of several research articles on science process skills of junior high school students, it is seen that the average results of the pretest scores. The average science process skills value of students from 2015 to 2020 is still low, which is around 41.07%. This research was conducted to see the effectiveness of the application of the guided inquiry learning model on students' science process skills in science subjects in junior high school. The method used for the study of literature is the analysis of several sources in the form of national research journals relating to the application of the guided inquiry learning model for science learning in junior high schools. Data analysis using the Miles & Huberman model, through the following stages; Record all the findings of the guided inquiry aspect and the results of the science process skills, Review the records of the documentation results, describe the classified data and make a final analysis in the form of a research report. Based on the analysis that has been carried out, it can be concluded that: 1) The guided inquiry learning model is effective in increasing the science process skills in science subjects in junior high schools in the medium category; 2) Materials about vibrations and waves are more effectively used with guided inquiry learning models than other materials to improve science process skills for junior high school students; 3) The guided inquiry learning model is effective, especially if it is used to improve the science process skills of junior high school students in the aspect of observing/ observing. Abstrak. Dari penelusuran beberapa artikel penelitian tentang Keterampilan Proses Sains (KPS) siswa SMP, terlihat hasil rata-rata nilai pretest. Nilai rata-rata KPS siswa Tahun 2015 sampai dengan Tahun 2020 masih rendah yaitu sekitarÂ  41,07%. Penelitian ini dilakukan ntuk melihat efektivitas penerapan model pembelajaran inkuiri terbimbingÂ  terhadap KPS siswa pada mata pelajaran IPA SMP. Metode yang digunakan untuk studi literatur yaitu analisis beberapa sumber berupa jurnal-jurnal penelitian nasional yang berkenaan dengan penerapan model pembelajaran inkuiri terbimbing untuk pembelajaran IPA di SMP. Analisis data menggunakan model Miles & Huberman, melalui tahapan-tahapan sebagai berikut; Mencatat semua temuan aspek inkuiri terbimbing dan hasil KPS, Menelaah kembali catatan hasil dokumentasi, Mendeskripsikan data yang telah diklasifikasikan dan Membuat analisis akhir dalam bentuk laporan hasil penelitian. Berdasarkan analisis yang telah dilakukan dapat disimpulkan bahwa: 1) Model pembelajaran inkuiri terbimbing efektif untuk meningkatkan KPS pada mata pelajaran IPA di SMP dengan kategori sedang; 2) Materi tentang getaran dan gelombang lebih efektif digunakan dengan model pembelajaran inkuiri terbimbing daripada materi lainnya untuk meningkatkan KPS siswa SMP; 3) Model pembelajaran inkuiri terbimbing efektif terutama jika digunakan untuk meningkatkan keterampilan proses sains siswa SMP pada aspek mengamati/ melakukan observasi. Â